Investigation of the Physical Education and Sport Teacher Candidates’ Attitudes towards Teaching Practice Course - Murathan, Fatih (Asian Journal of Education and Training, 2019)
It is known that the aims and achievements of the Higher Education Institution in the Teacher Education Guidelines of our country will enable the teacher candidates to develop a positive attitude from the professional point of view with the help of teaching practice course. In this context, Teaching practice course is a transformation of the theoretical knowledge acquired during the undergraduate course into practice. In the light of this information, it is aimed to examine and evaluate the professional attitudes of the last grade teacher candidates who are studying at the School of Physical Education and Sport in relation to the teaching practice course. A total of 128 female and 141 male candidate teachers who were educated in the 4th grade participated in the study as volunteers during the 2017-2018 academic year Spring semester in the Department of Physical Education and Sport Teaching. As a data collection tool " School Experience Lessons Scale of Attitude (ODDTÖ)’’ developed by Kılınç and Salman (2007) was used in the research. The Cronbach Alpha reliability co-efficient of scale is 0.94. As a result of the research, there was a statistically significant difference between the attitudes of the teacher candidates regarding the gender status, the university where they studied, and their attitudes towards teaching practice course. As a result, Teaching Practice courses are seen as very useful and important for teacher candidates. It can also be concluded that teaching practice is useful and necessary for professional experience by teacher candidates and this practice is seen as a necessary complementary factor to the profession.